2001
DOI: 10.1093/ajcn/73.2.456s
|View full text |Cite
|
Sign up to set email alerts
|

Effects of fructans-type prebiotics on lipid metabolism

Abstract: Several nondigestible but fermentable dietary carbohydrates are able to regulate lipemia and triglyceridemia in both humans and animals. The mechanism of their serum lipid-lowering effect remains to be elucidated. Oligofructose, which is a mixture of nondigestible and fermentable fructans, can decrease triacylglycerol in VLDL when given to rats. The triacylglycerol-lowering action of oligofructose is due to a reduction of de novo fatty acid synthesis in the liver through inhibition of all lipogenic enzymes, na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
91
1
12

Year Published

2009
2009
2014
2014

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(113 citation statements)
references
References 32 publications
9
91
1
12
Order By: Relevance
“…the level of cholesterol was also decreased in the liver plasma membranes of FOS-fed rats. This finding is in consistence with the reported hypocholesterolic effect of prebiotics (7). the decreased level of cholesterol might be another reason for the fluidization of the plasma membrane bilayer (Fig.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…the level of cholesterol was also decreased in the liver plasma membranes of FOS-fed rats. This finding is in consistence with the reported hypocholesterolic effect of prebiotics (7). the decreased level of cholesterol might be another reason for the fluidization of the plasma membrane bilayer (Fig.…”
Section: Resultssupporting
confidence: 89%
“…the obtained data showed that the total phospholipids were reduced in liver plasma membranes from FoS-fed rats. it is possible that this observation is related to reduced liver lipogenesis, which was reported by Delzenne and Kok (7). Among the key enzymes that control lipogenesis, fatty acid synthase (FAS) was found to be most markedly affected (10).…”
Section: Resultsmentioning
confidence: 78%
“…First, a decrease in glycemia could be part of the process since glucose (together with insulin) is a driver of lipogenesis. Secondly, the SCFAs produced through the fermentation process could play a role in the regulation of lipid metabolism (Delzenne and Kok 2001;Delzenne et al 2002).…”
Section: Effects On Serum Lipid and Cholesterol Concentrationsmentioning
confidence: 99%
“…In a 10-week study comparing obese and lean rats, adding 5 g of P. ovata to rat chow increased the phosphorylation of AMPK, consequently inhibiting acetyl-CoA carboxylase [50]. Fructooligosaccharide (10g/100g) also has been shown to decrease the hepatic acetyl-CoA carboxylase expression in rats [51]. In view of new research [52,34] the United States Food and Drug Administration has approved health claims supporting the role of dietary fiber in the prevention of coronary heart disease [53].…”
Section: Fiber Lipid Metabolism and Cardiovascular Diseasementioning
confidence: 99%